MEMAHAMI QUALITY ANSSURANCE MENJADIKAN BUDAYA MUTU PERGURUAN TINGGI (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
Since launched High Education Long Term (HELT 2003-2010), universities both public and private are required to conduct quality assurance systems. Implementation of quality assurance increased after the government provide assistance blockgrand to increase higher education quality assurance system. Quality assurance system consists of two types, there are internal quality assurance systems and external quality assurance systems. Higher education otherwise qualifed, if it is able to realize its vision through execution of it's mission, and able to meet the needs of stakeholders, such as the fulfllment of social needs, the needs of the world of work, and professional needs. On this basis, quality culture needs to be realized is not just a slogan, and only for the fulfllment of administrative requirements of acreditation but actually realized. This is a form of accountability to the public education institutions. For that it takes commitment from each of the elements in the glittering college and support facilities and infrastructure so that quality can continue to run.Keywords: quality, quality assurance assurance, and quality culture